School Security and Safety for Students with Special Needs in the Kingdom of Saudi Arabia - Al-Shahrani, Mohammed bin Nasser al-Maatiq (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed at evaluating the school safety and security which is necessary to protect students with special needs in Saudi Arabia. The analytical descriptive approach was used  and study was divided into two main chapters: The first chapter deals with the conceptual framework by identifying the meaning of school security and safety, and identifying the special needs group. Then in the next chapter the researcher analyzed the current reality in Saudi society and diagnose it. The negative effects of not integrating special needs students in schools, and concluding with the most important recommendations and mechanisms to remedy these problems, and design a plan of action to implement the study and set a timetable for it. Results: Children with special needs face several problems, including psychological, educational or social, and the integration of this group into society in general and in schools is a complex issue. Integration is defined as providing opportunities for children with disabilities to become involved in the special education system as a means of emphasizing the principle of equality Opportunities in education and aims to integrate in general to meet the special educational needs of children with disabilities within the framework of the regular school and according to the methods and methods and methods of educational studies and supervised by the provision of a specialized educational system in addition to the cadres of education in the public school and many studies pointed to the impact Consolidation and support, including those rejected as a result of several positive and negative trends.
Keywords: school security and safety; students; people with special needs